2016
DOI: 10.4238/gmr.15038036
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 9 facilitates osteocarcinoma cell apoptosis and inhibits in vivo tumor growth

Abstract: ABSTRACT. Osteosarcoma (OS) causes millions of death worldwide and, since there is no effective therapy, it is necessary to identify the molecular mechanism of OS, which can direct the development of new therapies. This study investigated the role of bone morphogenetic protein 9 (BMP9), a member of the transforming growth factor (TGF)-β family, in OS development. This study first examined BMP9 expression in tissue from OS patients and normal subjects. The OS cell line (MG63) and tumor cells from OS patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…We found that si-TGF-β treatment significantly decreased the viability of U2OS/MG-63 cells (P < 0.05; Figure 2(a-c)). TGF-β has been shown to play a role in modulating osteosarcoma cell apoptosis [36]. Our results show that TGF-β downregulation directly induces an increase in S-phase cell cycle arrest and upregulates the expression of apoptosis-related markers.…”
Section: Discussionmentioning
confidence: 52%
“…We found that si-TGF-β treatment significantly decreased the viability of U2OS/MG-63 cells (P < 0.05; Figure 2(a-c)). TGF-β has been shown to play a role in modulating osteosarcoma cell apoptosis [36]. Our results show that TGF-β downregulation directly induces an increase in S-phase cell cycle arrest and upregulates the expression of apoptosis-related markers.…”
Section: Discussionmentioning
confidence: 52%
“…Next, we explored the upstream key apoptosis-related protein–cysteine aspartate-specific protease (caspase-9). , Hep3B cells incubated with BDPBr 2 hardly expressed caspase-9 protein under light conditions, but when incubated with LBBr 2 NPs under light conditions, the expression of caspase-9 increased significantly. There was no significant difference in the expression of caspase-9 between free lenvatinib and LBBr 2 NPs without illumination.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It has been confirmed that BMP9, a potent osteogenetic factor, plays various roles in cancers. For example, BMP9 can inhibit the growth of lung adenocarcinoma [ 11 ], colon cancer [ 12 ], and osteocarcinoma [ 13 ], but exert a promotion effect on the proliferation and migration of liver cancer cell [ 14 ]. Additionally, in our previous research, we have found that BMP9 can inhibit the proliferation and migration of the breast cancer cell lines MDA-MB-231 [ 15 ] and SK-BR-3 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%